Stability of Molybdenum Back Electrode on Muscovite Substrate for Flexible Thin-Film Solar Cells - Syabriyana*, Maliya; Zulfajri, Muhammad; Maulinda, Maulinda; Akbar, Muhammad; Kumar, Nitin (Jurnal IPA & Pembelajaran IPA, 2025)
The stability of molybdenum (Mo) back contacts in thin-film solar cells is crucial, as oxidation and water ingress can degrade the device performance. This study examines the quality and aging stability of Mo electrodes on flexible muscovite substrates with various adhesion layer deposition pressures (0, 3, 5, and 10 sccm). The microstructure and crystal quality of Mo were analyzed, and film stability was evaluated by exposing samples to atmospheric conditions for eight weeks. Film morphology, reflectance, and resistivity were assessed using scanning electron microscopy (SEM), UV-Visible spectrometry, and four-point probe measurements. In addition, impurity diffusion from muscovite substrates was investigated. The results show that the adhesion layer significantly improved Mos microstructure and crystal quality. Mo electrode with an adhesion layer deposited at low pressure exhibited good stability against environmental exposure compared to those without an adhesion layer. Secondary ion mass spectrometry (SIMS) analysis revealed that in the absence of an adhesion layer, aluminum and silicon diffused into Mo after aging, whereas with an adhesion layer, alkali metal diffusion was observed